Budaya organisasi yang ideal bagi generasi Z - Hariyanto, Felik; Yanti, Bonita Eka Dama; Nugroho, Yohanes Agung Wahyu; Sahrah, Alimatus (PSYCOMEDIA : Jurnal Psikologi, 2025)
Technological advances in the Society 5.0 era require companies to continue to develop sustainably, relying on human resources as a key element of success. In this context, Generation Z, which dominates the world of work today, brings unique characteristics that influence work preferences, technology use, and social values. This demographic change presents challenges as well as opportunities for companies to create an ideal organizational culture for Generation Z. This study uses a Systematic Literature Review (SLR) approach to various scientific articles reviewed to analyze organizational culture that can support Generation Z employees in adapting and making optimal contributions in the world of work. The results of the review of twenty articles concluded that organizational culture influences employees, especially Generation Z. The ideal organizational culture for Generation Z employees is a culture that is inclusive, adaptive, and supports self-development and work-life balance. This culture does not only depend on one variable but involves various other factors. From this SLR research, it can later be used as a reference for all organizations/companies to improve organizational culture towards their employees, especially Generation Z